The Twazon Arabic Weight Loss App: App-Based Intervention for Saudi Women With Obesity - Alnasser, Aroub; Kyle, Janet; Aloumi, Najla; Al-Khalifa, Abdulrahman; Marais, Debbi (JMIR Publications, 2019)
BackgroundBy 2022, it is estimated that the rate of female obesity (78%) in Saudi Arabia will almost double that of males (41%). Despite being mainly attributed to poor diet, sedentary lifestyle, and a lack of health awareness, behavioral modification interventions are relatively new to the population; bariatric surgery continues to be the treatment of choice for comorbidities. However, neither pre nor postoperative diet and exercise are promoted. Evidence-informed mobile health (mHealth) weight loss apps and interventions may be an effective tool for delivering a culturally relevant intervention. ObjectiveThis study aimed to determine the feasibility of a weight loss intervention that tests the effectiveness of Twazon, an originally designed Arabic weight-loss app that promotes lifestyle modification specific to Arab populations. MethodsA pre-post single‐arm pilot study was carried out among a sample of 240 overweight volunteer Saudi women residing in Riyadh, Saudi Arabia who used the Twazon app over a 4-month period. Anthropometric, diet, and physical activity measures were assessed 3 times: baseline, 2-months and 4-months; frequency of app use and system usability were evaluated during the 2 latter data collection periods. Repeated measures analysis of variance was used to identify changes over time. ResultsA total of 40 participants completed the 4-month intervention with an attrition rate of 83%. An evaluation of the frequency of app use fostered 2 groups: engaged users (65%) and unengaged users (35%). At 4 months, the engaged users experienced more successful outcomes; body weight was lowered on average by 1.3 (SD 0.6) kg (P=.18), waist circumference (WC) was reduced by 4.9 (SD 1.1) cm (P<.001), and daily energy consumption was decreased by >600 calories (P=.002). Unengaged users experienced minor changes in body weight, WC, and reduced energy intake. ConclusionsThe findings have demonstrated that engagement with the Twazon app renders positive changes in body weight, WC, and energy intake. mHealth weight loss apps and interventions have the potential to be effective in promoting weight loss and healthy lifestyle modification in Saudi Arabia and similar populations.